Structural Insights Into the High Selectivity of the Anti-Diabetic Drug Mitiglinide - Wang, Mengmeng; Wu, Jing-Xiang; Chen, Lei (Frontiers in Pharmacology, 2022)
Mitiglinide is a highly selective fast-acting anti-diabetic drug that induces insulin secretion by inhibiting pancreatic KATP channels. However, how mitiglinide binds KATP channels remains unknown. Here, we show the cryo-EM structure of the SUR1 subunit in complex with mitiglinide. The structure reveals that mitiglinide binds inside the common insulin secretagogue-binding site of SUR1, which is surrounded by TM7, TM8, TM16, and TM17. Mitiglinide locks SUR1 in the NBD-separated inward-facing conformation. The detailed structural analysis of mitiglinide-binding site uncovers the molecular basis of its high selectivity.